2018
DOI: 10.4314/sajas.v48i5.2
|View full text |Cite
|
Sign up to set email alerts
|

Genomics for the advancement of livestock production: A South African perspective

Abstract: Most of the growth of human populations worldwide will be in developing countries, including South Africa. Natural resources are under immense pressure and animal scientists are faced with the challenges for increased efficiency and long-term sustainability of livestock production. Since the completion of the Human Genome Project, animal genomes have been mapped with genomics, enabling new opportunities for application in farm animal species. The use of microsatellite markers has made significant contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The genetic diversity among South African indigenous cattle breeds has been assessed using DNA markers (i.e., microsatellites and single nucleotide polymorphism) [24]. Makina et al [20] reported that the average genetic distance was lowest among indigenous (i.e., Afrikaner, Nguni, and Drakensberger) and locally developed (i.e., Bonsmara) breeds, and greatest between indigenous and exotic cattle breeds (i.e., Angus and Holstein).…”
Section: Genetic Diversity Of Cattle Breeds In Southern Africamentioning
confidence: 99%
“…The genetic diversity among South African indigenous cattle breeds has been assessed using DNA markers (i.e., microsatellites and single nucleotide polymorphism) [24]. Makina et al [20] reported that the average genetic distance was lowest among indigenous (i.e., Afrikaner, Nguni, and Drakensberger) and locally developed (i.e., Bonsmara) breeds, and greatest between indigenous and exotic cattle breeds (i.e., Angus and Holstein).…”
Section: Genetic Diversity Of Cattle Breeds In Southern Africamentioning
confidence: 99%
“…The well-established adaptations to prevailing environmental and management conditions exhibited by domestic free-range animal populations represent valuable genetic resources for improving breeds and the efficiency of animal production. Domestic free-range populations may add potential characteristic genetic variation, which could be valuable to producers in supplying new diversity for the improvement of commercial lines [16]. However, domestic free-range pigs were long regarded as unsuitable for intensive commercial breeding because of their slow growth and inadequate meat production [17].…”
Section: Origins and Description Of Domestic Free-range Pigs In Southmentioning
confidence: 99%
“…Other issues include overarching constraints that are external to the production system, which include conflicts, globalization, population growth, changing consumer tastes, religious taboos, developments in science and technology, and climate change. These will obviously impact conservation and use of AnGR in some way [16].…”
Section: Sustainable Utilization and Conservation Of Pig Genetic Resomentioning
confidence: 99%
See 2 more Smart Citations